The Influence of Religious Education on Adolescent Behavior - Muh Hanapi Bahri (Indonesian Journal of Education and Science, 2025)
Religious education plays a crucial role in shaping adolescent behavior by instilling moral values, fostering self-discipline, and preventing negative conduct. This study aims to analyze the influence of religious education on adolescent behavior, identify challenges in its implementation, and evaluate its effectiveness in preventing juvenile delinquency. Using a qualitative literature review approach, data were collected through document analysis of scholarly works, including journal articles, books, and research reports. The findings indicate that religious education significantly enhances adolescents' moral awareness, ethical decision-making, and prosocial behavior. However, challenges such as student disengagement, curriculum limitations, and external social influences hinder its effective implementation. Despite these challenges, religious education serves as a preventive mechanism against juvenile delinquency by fostering self-regulation, promoting ethical responsibility, and reinforcing positive character traits. This study underscores the need for a more integrated approach that combines religious education with mental health support to maximize its impact on adolescent behavior. The findings contribute to the fields of education and adolescent psychology by providing insights into strategies for strengthening the role of religious education in character development.